THE ROLE OF KNOWLEDGE MANAGEMENT AND EMPLOYEE COMPETENCY TOWARDS ORGANIZATION PERFORMANCE WITH INNOVATION AS A MEDIATING VARIABLES IN LOCAL WATER COMPANY (PDAM) KETAPANG REGENCY WEST KALIMANTAN - Endah Setyowati; Suharto; Iwan Kurniawan Subagja (International Journal of Business and Social Science Research, 2020)
This study aims to: 1) test and analyze the role of knowledge management and competence in innovation, 2) test and analyze the role of knowledge management and competence on organizational performance, 3) test and analyze the role of innovation on organizational performance, 4) test and analyze the role of management knowledge of organizational performance through innovation, 5) testing and analyzing the role of competence on organizational performance through innovation, and 6) testing and analyzing the role of knowledge management and employee competence on organizational performance through innovation at PDAM Ketapang Regency. The research was conducted by PDAM Ketapang Regency employees, totaling 71 employees. The sampling technique uses saturated samples. Methods of data analysis using descriptive analysis and quantitative analysis with path analysis. The results showed that: 1) there was an influence on the role of knowledge management and competence on innovation, 2) there was an influence on the role of knowledge management and competence on organizational performance, 3) there was an influence on the role of innovation on organizational performance, 4) there was an influence on the role of knowledge management on organizational performance through innovation, 5) there is an influence on the role of competence on organizational performance through innovation, and 6) there is an influence on the role of knowledge management and employee competence on organizational performance through innovation at PDAM Ketapang Regency.